Psychologiczne mechanizmy bezpieczeństwa zdrowotnego - Florczak, Agnieszka (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The article raises a subject of psychological mechanism of health safety. At the beginning of deliberations a term of health with its classic division was introduced. Health is not merely the absence of disease but also a state of physical, social and mental welfare. Hence, health can be divided into physical (somatic) and psychological. Health and safety are considered the most important value for human. Factors affecting health safety are primarily mental, physical and environmental. The article examines the first two. Somatic factors relate to purely biological aspects of life of an organism, while psychological to adaptability and societal. Through appropriate mechanisms psychosphere forms health safety on the one hand, but on the other the mechanisms in some interactions can pose problems that are explained more extensively in the last part of the work.